The Influence of Psychological Factors on Ethical Decision Making in Islamic Educational Institutions at Sma Plus Assalaam - Ahsyaf Muzakki; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article aims to examine the influence of psychological factors on ethical decision-making in Islamic educational institutions. The research method used in this article is qualitative with a descriptive approach. Data collection techniques include: first, in-depth interviews; second, participant observation; and third, documentation. The data collected through these three techniques were then validated through credibility checks. The research findings on the influence of psychological factors on ethical decision-making at SMA Plus Assalaam. The module project